Shear stress, arterial identity and atherosclerosis - Lehoux, Stephanie; Jones, Elizabeth A. (Thrombosis and Haemostasis, 2016)
In the developing embryo, the vasculature first takes the form of a web-like network called the vascular plexus. Arterial and venous differentiation is subsequently guided by the specific expression of genes in the endothelial cells that provide spatial and temporal cues for development. Notch1/4, Notch ligand delta-like 4 (Dll4), and Notch downstream effectors are typically expressed in arterial cells along with EphrinB2, whereas chicken ovalbumin upstream promoter transcription factor II (COUP-TFII) and EphB4 characterise vein endothelial cells. Haemodynamic forces (blood pressure and blood flow) also contribute importantly to vascular remodelling. Early arteriovenous differentiation and local blood flow may hold the key to future inflammatory diseases. Indeed, despite the fact that atherosclerosis risk factors such as smoking, hypertension, hypercholesterolaemia, and diabetes all induce endothelial cell dysfunction throughout the vasculature, plaques develop only in arteries, and they localise essentially in vessel branch points, curvatures and bifurcations, where blood flow (and consequently shear stress) is low or oscillatory. Arterial segments exposed to high blood flow (and high laminar shear stress) tend to remain plaque-free. These observations have led many to investigate what particular properties of arterial or venous endothelial cells confer susceptibility or protection from plaque formation, and how that might interact with a particular shear stress environment.
Keywords: Shear stress; endothelial cells; arteriovenous differentiation; atherosclerosis